Administrative activities as shown in the annual reports of vocational high school principals in Abra - Agcaoili, Andres B. 1930- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1967)
The aim of the study is to determine certain practices of administrators in Abra through the use of the principals' annual reports. The study has implications on leadership responsibility of the school administrator, and is a means of evaluating and measuring the administrative function of education.
Thesis (M.Ed.)--University of the Philippines
Keywords: School principals; School superintendents